OPTIMALISASI PENGGUNAAN PROYEKTOR DALAM PEMBELAJARAN PADA MATA PELAJARAN I.P.A (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2021)
The objectives to be achieved in this study are to determine the us of projector media in I.P.A learning and to determine the impact of using projector media in I.P.A learning. The use of projector learning media can help teachers develop teaching techniques so that they can get maximum result. Optimal use of the projector in the teaching and learning process, especially in science subjects, is expected to increase student motivation in learning. This research is a library research type with document data collection techniques in this study in the from of journals from previous research related to the us of projectors in I.P.A learning. From the discussion, it can be concluded that the us of projectors in I.P.A learning is useful as a presentation tool, as an information medium and as a video player. In additiom, the us of projector learning media in science subjects can increase student motivation in learning so that it has apositive impact in increasing student achievement.